Oreocharis glandulosa, a new species of Gesneriaceae from southern Yunnan, China - Tan, Yun-Hong; Li, Jian-Wu; Pan, Bo; Wen, Bin; Yin, Jian-Tao; Liu, Qiang (Phytotaxa, 2013)
Oreocharis glandulosa, a new species of Gesneriaceae from southern Yunnan, China, is here described and illustrated. It is similar to O. bodinieri in its corolla shape, but can be easily distinguished by its dense glandular pubescence on the outside of the corolla, the limb distinctly two-lipped, the adaxial lip bilobed to near base, the lobes ovate to triangular-ovate, the abaxial lip trilobed to the base, the included stamens, the glabrous anther connectives and the ring-like, glabrous, entire or subentire disc.